Outlook and Challenges of Nano Devices, Sensors, and MEMS - Li, Ting; Liu, Ziv (Springer International Publishing : Imprint: Springer, 2017)
This book provides readers with an overview of the design, fabrication, simulation, and reliability of nanoscale semiconductor devices, MEMS, and sensors, as they serve for realizing the next-generation internet of things. The authors focus on how the nanoscale structures interact with the electrical and/or optical performance, how to find optimal solutions to achieve the best outcome, how these apparatus can be designed via models and simulations, how to improve reliability, and what are the possible challenges and roadblocks moving forward.